Bakhtin and Buber: Problems of Dialogic Imagination - Nina Perlina (Studies in 20th & 21st Century Literature, 1984)
Recent publications of biographical materials on Mikhail Bakhtin demonstrate that he was familiar with the writings of Martin Buber. The philosophical and aesthetic verbal expression of Buber's ideas within the time-spatial universe of Bakhtin's own awareness allows us to discuss this obvious biographical evidence in a wider cultural context. The central opposition of Buber's and Bakhtin's systems is the dialogic dichotomous pair: "Ich und Du" (I and Thou), or "myself and another." Bakhtin's dialogic imagination is rooted in the binaries of the subject-object relations which he initially formulated as "responsibility" and "addressivity," that is to say, as individual awareness and its responsiveness of life. The basic words of Bakhtin's philosophical aesthetics can be understood as the "relation to the other," and their semantics and terminological meaning are directly related to Martin Buber (his work, Ich und Du, 1923). In the 1930s-60s Bakhtin developed the concepts of responsibility and addressivity into his universal dialogic theory of speech-genres. His hierarchy of speech-genres was built in order to establish relations between different sub-genres of the novel (various types of poetic utterances) and different species of individual discourse. However, the entire edifice of this dialogic system remained unfinished, and several types of dialogic relations between individual pronouncements of the characters and individual novelistic genres were not discussed by him. Buber's ideas on the dialogue can be used as a clue to one possible interpretation of the function of authoritative and internally persuasive discourses in different sub-genres of the novel (the novel of confession, the Bildungsroman, the autobiographical novel). In this article, Buber's philosophical cycle is used as an aid in reconstructing the integral whole of Bakhtin's "dialogic imagination," as this dialogic mode of thinking goes through his unfinished works: "Author and Hero in Aesthetic Activity," "The Bildungsroman and its Significance in the History of Realism," "Toward Reworking of the Dostoevsky Book."
Keywords: Russian literature; philosophy; Mikhail Bakhtin; Martin Buber; aesthetic; time-space; space; time; self; another; imagination; binaries; subject-object relations; discourse; dialogic imagination; Author and Hero in Aesthetic Activity; The Bildungsroman and its Significance in the History of Realism; Toward Reworking of the Dostoevsky Book